Tumour-associated glial host cells display a stem-like phenotype with a distinct gene expression profile and promote growth of GBM xenografts. Issue 1 (December 2017) - Leiss, Lina; Mutlu, Ercan; Øyan, Anne; Yan, Tao; Tsinkalovsky, Oleg; Sleire, Linda; Petersen, Kjell; Rahman, Mohummad; Johannessen, Mireille; Mitra, Sidhartha; Jacobsen, Hege; Talasila, Krishna; et al.
Abstract Background Little is known about the role of glial host cells in brain tumours. However, supporting stromal cells have been shown to foster tumour growth in other cancers. Methods We isolated stromal cells from patient-derived glioblastoma (GBM) xenografts established in GFP-NOD/scid mice. With simultaneous removal of CD11b+ immune and CD31+ endothelial cells by fluorescence activated cell sorting (FACS), we obtained a population of tumour-associated glial cells, TAGs, expressing markers of terminally differentiaed glial cell types or glial progenitors. This cell population was subsequently characterised using gene expression analyses and immunocytochemistry. Furthermore, sphere formation was assessed in vitro and their glioma growth-promoting ability was examined in vivo. Finally, the expression of TAG related markers was validated in human GBMs. Results TAGs were highly enriched for the expression of glial cell proteins including GFAP and myelin basic protein (MBP), and immature markers such as Nestin and O4. A fraction of TAGs displayed sphere formation in stem cell medium. Moreover, TAGs promoted brain tumour growth in vivo when co-implanted with glioma cells, compared to implanting only glioma cells, or glioma cells and unconditioned glial cells from mice without tumours. Genome-wide microarray analysis of TAGs showed an expression profile distinct from glial cells from healthy mice brains. Notably, TAGs upregulated genes associated with immature cell types and self-renewal, includingPou3f2 andSox2 . In addition, TAGs from highly angiogenic tumours showed upregulation of angiogenic factors, includingVegf andAngiopoietin 2 . Immunohistochemistry of three GBMs, two patient biopsies and one GBM xenograft, confirmed that the expression of these genes was mainly confined to TAGs in the tumour bed. Furthermore, their expression profiles displayed a significant overlap with gene clusters defining prognostic subclasses of human GBMs. Conclusions Our data demonstrate that glial host cells in brain tumours are functionally distinct from glial cells of healthy mice brains. Furthermore, TAGs display a gene expression profile with enrichment for genes related to stem cells, immature cell types and developmental processes. Future studies are needed to delineate the biological mechanisms regulating the brain tumour-host interplay.